Serological and Molecular Detection of Bartonella henselae in Cats and Humans From Egypt: Current Status and Zoonotic Implications - Sayed, Amal S. M.; Alsaadawy, Reem M.; Ali, Magda M.; Abd El-Hamid, Rawhia F.; Baty, Roua Sami; Elmahallawy, Ehab Kotb (Frontiers in Veterinary Science, 2022)
Bartonellosis is a vector-borne zoonotic disease caused by the intracellular bacterium of genus Bartonella. The disease has a worldwide distribution and cats represent the major reservoir of this disease. Despite its global distribution, very limited previous studies have investigated the occurrence of bartonellosis in cats and their owners in Egypt. In an endeavor to explore this topic, we investigated the occurrence of Bartonella henselae (B. henselae) infection in 225 samples (blood, saliva, and claw) obtained from 75 healthy cats in Upper Egypt. These samples were routinely obtained during veterinary clinic visits. This study also involved an examination of 100 humans, including cat owners and people with a history of contact with cats. Attempted isolation and identification of B. henselae in cats were also performed. Furthermore, PCR was performed for molecular identification of B. henselae in blood samples from cats. Meanwhile, an immunofluorescent assay was performed to study the seroprevalence of B. henselae infection in humans. In this study, B. henselae could not be isolated from any of the examined blood, saliva, or claw samples from cats. Interestingly, B. henselae was identified molecularly in 8% (6/75) of blood samples from cats. The seroprevalence of B. henselae in humans was 46% and its occurrence was higher in females (46.6%) than in males (41.7%) (P = 0.748). B. henselae infection was higher among cat owners [51.4% (19/37)] than among people with a history of contact with cats [42.9% (27/63)] (P = 0.410). Infection was higher in rural regions [79.5% (31/39)] than in urban regions [24.6% (15/61)] (P < 0.001). Collectively, this data provide interesting baseline information about the occurrence of B. henselae in cats and humans in Upper Egypt, which reflects the potential zoonotic transmission of this bacterium. Future study is mandatory to explore the occurrence of B. henselae in major reservoirs in Egypt.